A Low Distortion Radiation Pattern Ultra-Wideband TEM Horn Antenna - Mahdi Zoghi; Farrokh Hodjatkashani; Mir Emad Lajevardi (IEEE Open Journal of Antennas and Propagation, 2024)
This paper introduces a low distortion radiation pattern ultra-wideband (UWB) transverse electromagnetic (TEM) horn antenna designed to operate in the 2 to 18 GHz frequency range. The modification is achieved using a non-uniform antenna feed without changing the antenna’s flare structure. The main-lobe radiation pattern of the antenna at higher frequencies eliminates ripples by using a non-uniform feeding technique compared to conventional TEM horn antennas, in which this issue exists. The measurement results pursue simulation results with a good agreement. The maximum measurement ga in of the antenna is 15 dBi for the operating range, and a voltage standing ratio (VSWR) of 1:2 has been obtained in the whole frequency band. The final dimensions of the fabricated antenna with the feed section are defined as $3.65\, λ _{0} × 2\, λ _{0} × 2\, λ _{0}$ compared to the previous studies, have smaller dimensions in terms of the free-space wavelength and low distortion, and no fluctuation in the main lobe in the H and E-plane of the radiation pattern between 2 to 18 GHz. The maximum measured ripple of the proposed TEM horn antenna at the main lobe is equal to 0.3 dB. These mentioned features of the proposed antenna are used as a part of ultra-wideband systems.